Pendekatan Inquiry Learning dalam Perspektif QS. Al-Mulk Ayat 10: Analisis Kajian Tafsir Tarbawi - Saepudin Muzakki, Rifqi Fathan; Cucu Surahman; Elan Sumarna; Restu Rizki Amanda; Faiz Aswa Nazhan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This research explores the application of the Inquiry Learning method with an approach based on Qur'anic values, especially QS. Al-Mulk verse 10 as an effort to enrich the learning process with a spiritual dimension. In the Islamic view, Inquiry Learning not only aims to improve critical and analytical thinking skills, but also becomes a means of religious reflection that helps students integrate science with deep spiritual understanding. QS. Al-Mulk verse 10, which emphasizes the importance of using the mind and heart to understand the signs of Allah's greatness, is a strong basis for building a learning approach. Through a library research approach, this study explores Qur'anic commentaries and relevant scientific literature to understand how the values contained in the verse can be implemented in modern learning. The research findings show that the application of Inquiry Learning method based on QS. Al-Mulk verse 10 can improve students' ability to think critically, logically, and systematically, while leading them to contemplate the relationship between science and the existence of God. This not only broadens students' intellectual horizons but also strengthens their religious awareness, morals, and Islamic character. The implementation of this method is expected to form a generation that is not only academically superior, but also has a strong value foundation to face the challenges of the times with Islamic principles.